From science to policy practice and public discourse: Claimsmaking and chlorinated drinking water - Driedger, Michelle Suzanne (My University, 2001)
Since the rise of the environmental movement in the 1960s, public attention became focused on issues of ecosystem and human health. Since that time, there has been a growing public mistrust of industry, policymakers, and scientists. This research focuses on process-oriented issues in an area of scientific and regulatory 'uncertainty': chlorinated disinfection byproducts (CDBPs) and cancer outcomes. There are four objectives in this research. Scientific evidence regarding CDBPs and cancer is examined to explore how it has been constructed (objective 1). Further, the contesting of this evidence within the scientific community and its transformation to 'scientific fact' as 'authorities' is examined (objective 2). The impact these contested scientific authorities may have on the policymaking process in terms of setting guidelines, regulations, policies, and standards in both Canada and the United States is assessed (objective 3). Lastly, media presentations of scientific evidence as compared to framings by scientists, regulators, the chlorine industry, water utility representatives and environmental non-governmental organizations of the CDBP issue is investigated (objective 4). To address these objectives, this thesis adopts a mixed method approach by combining claimsmaking activities, narrative policy analysis, agenda-setting, and the use of language and metaphors to analyze the textual data. This thesis concludes that although the hegemony of science is challenged, the interpretation and use of scientific claims are increasingly important to establish authority and credibility on risk issues. Risk controversies are not going to disappear. These science-policy risk issues cannot be analyzed from a strict interpretation of 'science'. A 'social' lens must be brought in to understand the underlying political, social and cultural context of an issue. Risk controversies will not always take the same form in all places, and responses to these controversies must be sensitive to contextual differences. This thesis makes a number of substantive, methodological and theoretical contributions. Substantively, this research provides a detailed case study of a single uncertain and complex issue that links environment and health: CDBPs and cancer outcomes. The case study outlines how the issue has developed in two different regulatory environments (Health Canada and the US Environmental Protection Agency). Methodologically, this thesis incorporates multiple qualitative methods in its analysis of key informant interviews and written scientific, legal and policy documents. Theoretically, this research provides a conceptual model by which other environmental risk issues can be compared with respect to scientific uncertainty in the environmental health policy process.
Keywords: Geography; Geography